Impact of ChatGPT and LMS on Student Satisfaction, Engagement, and Self-Directed Learning : a Conceptual Paper - Saleh, Yusril; Widodo, Arry; Rubiyanti, R. Nurafn; Silvianita, Anita (Journal of Finance and Business Digital, 2024)
This study explores the integration of ChatGPT and Learning Management Systems (LMS) to enhance student satisfaction, engagement, and self-directed learning. ChatGPT provides personalized, interactive support, while LMS offers structured, collaborative tools, creating a comprehensive learning experience. Grounded in the Technology Acceptance Model (TAM) and Self-Determination Theory (SDT), the research proposes a framework linking ChatGPT and LMS usage to improved outcomes. This integration addresses gaps in traditional learning approaches, fostering dynamic and adaptive education. The findings highlight the transformative potential of combining AI-driven tools and digital platforms, offering actionable strategies for educators and policymakers. Future research should empirically validate this framework across varied educational contexts to optimize learning environments and improve teaching effectiveness.